2021
DOI: 10.3390/membranes11020116
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Isotherm Study of As(III) Removal from Aqueous Solution by PET Track-Etched Membranes Loaded with Copper Microtubes

Abstract: This paper reports on the synthesis and structure elucidation of track-etched membranes (TeMs) with electrolessly deposited copper microtubes (prepared in etched-only and oxidized polyethylene terephthalate (PET) TeMs), as well as on the comparative testing of arsenic (III) ion removal capacities through bath adsorption experiments. The structure and composition of composites were investigated by X-ray diffraction technique and scanning electron and atomic force microscopies. It was determined that adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
(105 reference statements)
1
17
0
Order By: Relevance
“…Correlation coefficients (R 2 ), linearized equations, and parameters calculated from these models are summarized in Table 1 . The data for both samples fit well with the pseudo-second-order model, confirming the literature data on the adsorption mechanism of As(III) by other composite sorbents such as Cu@PET composite TeMs [ 35 ], zeolite-reduced graphene oxide composite [ 87 ], and copper oxide-incorporated mesoporous alumina [ 88 ]. Intraparticle diffusion model was studied to understand whether the transport and diffusion of adsorbate is a rate-determining step.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Correlation coefficients (R 2 ), linearized equations, and parameters calculated from these models are summarized in Table 1 . The data for both samples fit well with the pseudo-second-order model, confirming the literature data on the adsorption mechanism of As(III) by other composite sorbents such as Cu@PET composite TeMs [ 35 ], zeolite-reduced graphene oxide composite [ 87 ], and copper oxide-incorporated mesoporous alumina [ 88 ]. Intraparticle diffusion model was studied to understand whether the transport and diffusion of adsorbate is a rate-determining step.…”
Section: Resultssupporting
confidence: 83%
“…PDMAEMA is a water-soluble cationic polymer with tertiary amine functional groups prone to complexation with arsenic. Another approach to remove fairly high amounts of As(III) is to use nanoparticles (NPs) of metal oxides [ 24 ], such as TiO 2 [ 25 , 26 , 27 ], Fe 2 O 3 [ 28 ], Fe 3 O 4 [ 29 , 30 ], CeO 2 [ 31 ], CeO 2 -ZrO 2 [ 32 ], CuO [ 33 ], Cu/CuO [ 34 , 35 ], Al 2 O 3 [ 36 ], ZrO 2 [ 37 ], and CaO 2 [ 38 ]. Zerovalent metal NPs such iron NPs [ 39 ], palladium NPs [ 40 ], and silver (Ag) NPs [ 41 , 42 ] have also been shown to be effective in As(III) removal.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, composite TeMs based on metals of the copper subgroup demonstrated high catalytic activity in various reactions types in both batch and flow-through modes [ 34 , 35 , 36 , 37 ]. For example, Ag/PET composites have proven to be effective photocatalysts for the removal of methylene blue dye [ 38 ], while CuO-based MTs have been shown to exhibit high efficiency in the sorption of As(III) ions [ 34 , 39 ]. Some important advantages of such catalysts and sorbents are their ease of use, low cost and ease of production, as well as the possibility for multiple reuses without additional activation and regeneration procedures, as shown in previous studies [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The model parameters were calculated from the ln ( qe ) graph versus the Polyanyi potential ε = RT ln (1 + 1/ Ce ). The average free energy of adsorption ( E , kJ/mol), which characterizes the free energy of the system due to the transfer of one mole of ions from the solution to the solid surface [ 70 ], was calculated from the B D values using the following Equation (11): …”
Section: Methodsmentioning
confidence: 99%